2007
DOI: 10.1073/pnas.0705079104
|View full text |Cite
|
Sign up to set email alerts
|

Complement factor H deficiency in aged mice causes retinal abnormalities and visual dysfunction

Abstract: Age-related macular degeneration is the most common form of legal blindness in westernized societies, and polymorphisms in the gene encoding complement factor H (CFH) are associated with susceptibility to age-related macular degeneration in more than half of affected individuals. To investigate the relationship between complement factor H (CFH) and retinal disease, we performed functional and anatomical analysis in 2-year-old CFHdeficient (cfh ؊/؊ ) mice. cfh ؊/؊ animals exhibited significantly reduced visual … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
142
3
2

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 197 publications
(164 citation statements)
references
References 34 publications
9
142
3
2
Order By: Relevance
“…Dysregulation of the complement system in mouse on the other hand has been associated with changes in retinal structure and function (63,64), alterations in retinal perfusion (65); but no data are available on UPR or lipid dysregulation in that context. Complement activation on RPE cells has been shown to lead to VEGF secretion followed by loss of barrier function (46,66) as well as secretion and activation of membrane metalloproteinases (58).…”
Section: Discussionmentioning
confidence: 99%
“…Dysregulation of the complement system in mouse on the other hand has been associated with changes in retinal structure and function (63,64), alterations in retinal perfusion (65); but no data are available on UPR or lipid dysregulation in that context. Complement activation on RPE cells has been shown to lead to VEGF secretion followed by loss of barrier function (46,66) as well as secretion and activation of membrane metalloproteinases (58).…”
Section: Discussionmentioning
confidence: 99%
“…53 The connection of the complement system to AMD has been reported in some murine models of dry-type AMD. 25,44,51,52,54,57,62 Retinal abnormalities have been described in aged FH deficient (Cfh À/À ) mice. 51 However, the disease phenotype was modest because these animals displayed a partial phenotype of dry AMD.…”
Section: Discussionmentioning
confidence: 99%
“…Electron microscopy revealed that in Cfh À/À mice there was no loss of photoreceptors. 51 The authors suggested that apical secretion of FH is important in maintaining complement regulation in the retina of these mice. However, Cfh À/À mice have negligible AP activating capacity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mice with a knock-out of complement factor H (Cfh Ϫ/Ϫ ) showed only thinning of Bruch membrane, lipofuscin deposition, and disorganized photoreceptor outer segments at the advanced age of 24 months (69). Although the pathology of AMD very likely involves inflammatory reactions, the molecular mechanisms that induce them remain largely unknown.…”
Section: Ccr2mentioning
confidence: 99%